Glycemic index and glycemic load of brief sugary sweets: randomized controlled trials of eight Thai desserts - Namjud, Nuttaphat; Senaprom, Sayamon; Ondee, Thunnicha; Bumrungpert, Akkarach; Heath, Julia; Pongpirul, Krit (Frontiers in Nutrition, 2024)
Background Thai desserts, celebrated for their exquisite sweetness, are widely enjoyed for personal indulgence and as cherished souvenirs. However, their high sugar content raises concerns regarding health impacts. This study aimed to quantify the glycemic index (GI) and glycemic load (GL) in healthy volunteers following consumption of various Thai desserts, out of 10 renowned desserts from across Thailand, identified by the Tourism Authority of Thailand, characterized by differing sugar levels. Method Eight were selected based on the absence of preservatives and microbial or chemical contaminations. Each participant consumed a 50-g serving of available carbohydrate (50avCHO) from these desserts. Ninety-six healthy volunteers, with a mean age of 31.8 ± 5.7 years, a mean body weight of 57.2 ± 7.3 kg, and 63.5% women, were randomized into eight groups, with each group comprising 12 participants. Blood samples were collected pre-and post-consumption to assess GI and GL values following established protocols. Results The findings revealed that Phetchaburi’s Custard Cake exhibited the lowest GI and GL values (53.4 and 26.7, respectively), with progressively higher values observed in Saraburi’s Curry Puff (61.8 and 30.9), Nakhon Sawan’s Mochi (68.9 and 34.4), Suphan Buri’s Sponge Cake (75.9 and 38.0), Ayutthaya’s Cotton Candy (81.4 and 40.7), Prachuap Khiri Khan’s Pineapple Cheese Cake Biscuit (87.4 and 43.7), Chon Buri’s Bamboo Sticky Rice (109.3 and 54.7), and Lampang’s Crispy Rice Cracker (149.3 and 74.7), respectively. Conclusion The study demonstrates that while Thai desserts exhibit a range of GI values, their GL values are uniformly high. It underscores the importance of disseminating GI and GL information to consumers, enabling them to make informed dietary choices and moderate their intake of these sugary delicacies.